Neurotrophins‐3 plays a vital role in anti‐apoptosis associated with NGF and BDNF regulation in neonatal rats with hypoxic‐ischemic brain injury. Issue 2 (28th June 2020) - Xiao, Qiu‐Xia; Chen, Jun‐Jie; Fang, Chang‐Le; Su, Zhang‐Yu; Wang, Ting‐Hua
Abstract : Objective: To explore the role of Neurotropfin‐3 (NT‐3) in hypoxic‐ischemic encephalopathy (HIE) and determine its relative molecular mechanism. Methods: The expression of NT‐3 was determined by qRT‐PCR in the cortex after HIE and immunofluorescence staining was used to detect the distribution of NT‐3. Then, the NT‐3 siRNA was used to validate the effect of NT‐3 for the neuroprotection by the measurement of cell apoptosis after oxygen‐glucose deprivation (OGD). Lastly, the molecular network mechanism was studied by NT‐3 interference experiment combined with bioinformatics technology. Results: The expression of NT‐3 was significantly upregulated after HIE, and NT‐3 was co‐localized in the neurons of the cortex. Furthermore, the inhibition of NT‐3 increased neuronal apoptosis after OGD and elicited the down‐regulation of BDNF and NGF. Conclusion: NT‐3 is a vital neurotrophic factor that can maintain neonatal survival in cortical neurons, and the underlying mechanism is associated with BDNF and NGF regulation.